The evolution of low-mass, close binary systems with a neutron star component: a detailed grid - De Vito, María Alejandra (2012)
In close binary systems composed of a normal donor star and an accreting neutron star, the amount of material received by the accreting component is, so far, a real intrigue. In the literature, there are available models that link the accretion disc surrounding the neutron star with the amount of material it receives, but there is no model linking the amount of matter lost by the donor star to that falling on to the neutron star. In this paper, we explore the evolutionary response of these close binary systems when we vary the amount of material accreted by the neutron star. We consider a parameter β which represents the fraction of material lost by the normal star that can be accreted by the neutron star. β is considered as constant throughout the evolution. We have computed the evolution of a set of models considering initial donor star masses M i/M ⊙ between 0.5 and 3.50, initial orbital periods P i/d between 0.175 and 12, initial masses of neutron stars (M NS) i/M ⊙ of 0.80, 1.00, 1.20 and 1.40 and several values of β. We assumed solar abundances. These systems evolve to ultracompact or to open binary systems, many of which form low-mass helium white dwarfs. We present a grid of calculations and analyse how these results are affected upon changes in the value of β. We find a weak dependence of the final donor star mass on β. In most cases, this is also true for the final orbital period. The most sensitive quantity is the final mass of the accreting neutron star. As we do not know the initial mass and rotation rate of the neutron star of any system, we find that performing evolutionary studies is not helpful for determining β.